Vocational Training: Does it speed up the Transition Rate out of Unemployment? - Bart Cockx; Isabelle Bardoulat (Tinbergen Institute, 2000)
In this paper we estimate, for the 1989-93 period in Belgium, the effect of vocational classroom training on therate of transition out of unemployment. We show that rationing of the demand for training increases theunemployment duration of non-participants, an effect neglected in programme evaluations. We propose a controlfunction estimator accounting for variable treatment effects and identifying the average treatment effect on thetreated by means of exogenous sub-regional variation in the training capacities. During participation, thetransition rate decreases by 27%. Afterwards it increases by 62%. Making training available for a broader populationwould, however, reduce the effectiveness of the programme.
Keywords: C41; J24; J64; J68; 330; Vocational training; evaluation; transition models; job-search; Berufsbildung; Arbeitslosigkeit; Schätzung; Belgien